Globalización financiera y desarrollo nacional - Ffrench-Davis Muñoz, Ricardo (Estudios Internacionales, 2006)
Globalization brings benefits and costs, in varying proportions, in various dimensions and circumstances. The relationship between costs and benefits depends on the level of development of each country, on the international norms that regulate globalization and, quite often, on the quality of national policies. Therefore, it is necessary to distinguish between the various components, with different implications, to identify those that may be more functional for national development, in order to enhance them, and to minimize those that create obstacles. And it is that globalization involves benefits and costs, which are not in a closed, immutable package. We can choose the content and proportions of the package to improve the quality of our international insertion.